2019
DOI: 10.1186/s13104-019-4604-6
|View full text |Cite
|
Sign up to set email alerts
|

Type of bacterial isolates and antimicrobial resistance profile from different clinical samples at a Referral Hospital, Northwest Ethiopia: five years data analysis

Abstract: Objective Antimicrobial resistance (AMR) is one of the most serious global public health threats that exert a significant burden in terms of patient morbidity and mortality and financial crises in many developing countries including Ethiopia. Knowledge on the type of predominantly circulating pathogens with their respective AMR profile in a given area is essential for optimal patient care. This study was aimed at assessing the types of bacterial isolates and their AMR profile identified from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 18 publications
6
27
7
Order By: Relevance
“…All 19 of the bacterial strains also exhibited the highest resistance to septrin, chloramphenicol, augmentin and streptomycin for urine specimens while 7 strains of P. aeruginosa exhibited the least resistance to sparfloxacin. Similarly, P. aeruginosa isolated from urine, and wound swabs was found resistant to chloramphenicol which corroborated the findings of this study [27][28]. This might be connected to the self medication of this drug implicated in this study.…”
Section: Resultssupporting
confidence: 90%
“…All 19 of the bacterial strains also exhibited the highest resistance to septrin, chloramphenicol, augmentin and streptomycin for urine specimens while 7 strains of P. aeruginosa exhibited the least resistance to sparfloxacin. Similarly, P. aeruginosa isolated from urine, and wound swabs was found resistant to chloramphenicol which corroborated the findings of this study [27][28]. This might be connected to the self medication of this drug implicated in this study.…”
Section: Resultssupporting
confidence: 90%
“…Indeed, this practice is a risk for development of antimicrobial resistance in most developing countries. In Ethiopia, where there are regulatory hindrances the challenge of antimicrobial resistance continued beside the scarcely available data 5 . The previous study has already reported the existence of elevated antimicrobial resistance (AMR) to different isolates, erythromycin (89.4%), amoxicillin (86.0%) and tetracycline (72.6%).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the most significant number of bacterial species was possible through the use of non-selective media: BHI and MH, which allow the isolation of a wide variety of microorganisms. These media have been successfully used to isolate bacteria from clinical specimens [ 28 , 29 ]. Compared to other culture media, BHI was the only one that enabled the isolation of Lactobacillus pentosus and Providenciastuartii .…”
Section: Resultsmentioning
confidence: 99%